Integrating Socio-Digital Skills in the Industry 4.0 era for graduates' employability: An employers’ perspective - Ainol Mardhiyah, Rahmat; Idaya Husna, Mohd; Muhamad Khalil, Omar; Rosemaliza, Kamalludeen; Wan Mohd Zulhafiz, Wan Zahari; Nurhidayah, Azmy; Airil Haimi, Mohd Adnan (JPSP, 2022)
The technological changes brought by the fourth industrial revolutions heavily impacted business environments and created a perfect storm in the employment market, prompting a need to explore the implications of changes in job demands and skills requirements. The debate remains to focus on graduate skills and employability, increasingly robust competition with experienced and skilful workers, changing skills due to technological changes. Identification of integration of skills is both essential and difficult. Considering that Industry 4.0 is still in Malaysia's early stage, this research intends to elucidate the exact integration of skills in the Industry 4.0 environment. This research adopts a qualitative methodology to explore the employment trend in the Industry 4.0 landscape. A qualitative research method is adopted, considering economies and labour-market experts do not yet know the exact mix or level of skills that particular occupations will demand. The findings revealed that employers value fresh graduates’ effort to integrate social and digital skills, leading to greater employability opportunities. The graduates must be able to coherent narrative shows to influence and convince the employer that they possess the right integration of skills to fit the organisation's culture and goals. Future job demands allow graduates to gain employability and compete with experienced candidates in a digital environment. What sets the graduates apart and gives them a competitive advantage is constructing strong socio-digital skills. The graduates must be able to coherent narrative shows to influence and convince the employer that they possess the right integration of skills to fit the organisation's culture and goals.